Global continuity and higher integrability of a minimizer of an obstacle problem under generalized Orlicz growth conditions - Arttu Karppinen (Springer, 2022)
We prove continuity up to the boundary of the minimizer of an obstacle problem and higher integrability of its gradient under generalized Orlicz growth. The result recovers similar results obtained in the special cases of polynomial growth, variable exponent growth and produces new results for Orlicz and double phase growth.